Penyalahgunaan Kekuasaan di Dalam Organisasi Kerja - Wahyuadianto, Agus (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2008)
Power abuse is a misuse of power which is granted to person. If it was informal usually will not make huge effect, but if it was a power is given by government then the destruction effect will broader because it is connected with more people. We can take Attorney Urip Tri gunawan who senteced 20 years and imprisoned and Rp 500 million penalties, for taking bribery worth US$ 6,000 for Bantuan Likuiditas Bank Indonesia II case. He used his power as the investigator chieff for that case to win the accused. This action can be categorised as organisational politic as well. Because he tried to fulfil his personal aims, even though they were contradicted with his organisation aims, in this case General Attoney. Organisational politic happens in every organisation in various intensity. But it gives more negative effects than the positive ones. Therefore it thas to be controlled from destroy organisation performance and keep the organisational misbehaviour called, workplace psychopath. This term refer to psychopathic activity inside organisation which destroy personnel psychologically.